Effect of early feed restriction and enzyme supplementation on digestive enzyme activities in broilers - Pinheiro, D. F. [UNESP]; Cruz, V. C. [UNESP]; Sartori, J. R. [UNESP]; Paulino, M. L. M. Vicentini [UNESP] (Poultry Science Assoc Inc, 2004)
The effect of feed restriction and enzymatic supplementation on intestinal and pancreatic enzyme activities and weight gain was studied in broiler chickens. Quantitative feed restriction was applied to chickens from 7 to 14 d of age. An enzyme complex mainly consisting of protease and amylase was added to the chicken ration from hatching to the end of the experiment. Birds subjected to feed restriction whose diet was not supplemented showed an increase in sucrase, amylase, and lipase activities immediately after the restriction period. Amylase, lipase, and chymotrypsin activities were higher in chickens subjected to feed restriction and fed a supplemented diet than in those only subjected to feed restriction. Trypsin activity increased after feed restriction and after supplementation, but there was no interaction between these effects. Early feed restriction had no effect on enzyme activity in 42-d-old chickens. Chickens subjected to early restriction and fed the supplemented diet presented higher sucrase, maltase, and lipase activities than nonsupplemented ones (P < 0.05). There was no effect of early feed restriction or diet supplementation on weight gain to 42 d. Percentage weight gain from 14 to 42 d of age was equivalent in feed-restricted and ad libitum fed birds. Feed-restricted broilers fed a supplemented diet showed a higher percentage weight gain than nonsupplemented birds. We conclude that enzymatic supplementation potentiates the effect of feed restriction on digestive enzyme activity and on weight gain.
Keywords: broiler; digestive enzyme; enzymatic supplementation; feed restriction